Opportunities for dietitians to promote a healthy dietary intake in pregnant women with a low socio-economic status within antenatal care practices in the Netherlands: a qualitative study - Sabina Super; Yvette H. Beulen; Maria A. Koelen; Annemarie Wagemakers (BMC, 2021)
Abstract Background A healthy dietary intake during pregnancy is important for maternal and child health. However, pregnant women with a low socio-economic status often fail to meet dietary guidelines and requirements for healthy nutrition. Dietitians may play an important role in providing nutritional advice during pregnancy because midwives often experience a lack of nutritional knowledge, time and skills to provide adequate advice. However, there is limited research on the support that dietitians can offer in antenatal care practices for pregnant women. Therefore, this study aims to explore the opportunities for dietitians to support pregnant women with a low socio-economic status in concurrent antenatal care practices in the Netherlands. Methods In-depth interviews were conducted with 14 pregnant women with a low socio-economic status and 13 dietitians to identify barriers for healthy eating for pregnant women and the associated opportunities for dietitians to support these women in making healthy dietary changes. Results Four opportunities for dietitians to support pregnant women in making dietary changes could be discerned: (1) creating awareness of healthy and unhealthy eating patterns, (2) providing reliable and personally relevant information, (3) help identifying barriers and solutions for healthy eating and (4) making healthy eating manageable. Dietitians indicated that supporting pregnant women with a low socio-economic status in consuming a healthy diet requires the investment of sufficient time, effort and money. Conclusions Dietitians are trained and well-equipped to provide extensive support to pregnant women to promote a healthy dietary intake, especially when the complex interplay of barriers that pregnant women with a low socio-economic status experience for healthy eating needs to be addressed. In addition, there is a strong need for strengthening the collaboration between dietitians and midwives because midwives are the primary care provider for pregnant women in the Netherlands, but they often lack sufficient opportunities to provide adequate nutrition support. Strengthening this collaboration could promote that nutrition becomes a recurring and standard topic in antenatal care.